2000
DOI: 10.1042/bj3510537
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel 45 kDa protein (JP-45) from rabbit sarcoplasmic-reticulum junctional-face membrane

Abstract: Using a biochemical/immunological approach to analyse the protein constituents of skeletal-muscle junctional-face membrane (JFM), we identified a 45kDa protein. Its N-terminal amino acid was blocked, but the amino acid sequence obtained from several peptides after proteolytic treatment did not significantly match that of any protein present in the SwissProt and NCBI (National Center for Biotechnology Information) databases. We synthesized a peptide whose sequence matched that of one of the peptides obtained af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…In the past few years a number of investigators have begun to define the major and minor structural components of the junctional face membrane (Ito et al, 2001;Takeshima et al, 2000). In previous studies (Zorzato et al, 2000;Anderson et al, 2003), we identified and characterized -at the biochemical and molecular level -JP-45, an integral membrane protein constituent of the SR junctional face membrane in skeletal muscle. We also showed that JP-45 colocalizes with the RyR Ca 2+ -release channel and interacts with Ca v 1.1 and the luminal Ca 2+ -binding protein calsequestrin (Anderson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years a number of investigators have begun to define the major and minor structural components of the junctional face membrane (Ito et al, 2001;Takeshima et al, 2000). In previous studies (Zorzato et al, 2000;Anderson et al, 2003), we identified and characterized -at the biochemical and molecular level -JP-45, an integral membrane protein constituent of the SR junctional face membrane in skeletal muscle. We also showed that JP-45 colocalizes with the RyR Ca 2+ -release channel and interacts with Ca v 1.1 and the luminal Ca 2+ -binding protein calsequestrin (Anderson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the RyR, however, the junctional face membrane contains numerous other proteins that, because of their anatomical location, are deemed to be involved in E-C coupling (Zhang et al, 1997;Costello et al, 1986;Zorzato et al, 2000). In the past few years a number of investigators have begun to define the major and minor structural components of the junctional face membrane (Ito et al, 2001;Takeshima et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the calcium-release channel (RyR), the SR and T tubule membranes also have a variety of proteins that, because of their subcellular location, are thought to contribute to ECC (23,24). They are involved in (i) calcium storage (calsequestrin) (25), (ii) signal transduction (triadin TD, junctin JC, mitsugumin-29, JP45) (23,24,26,27), (iii) calcium homeostasis (Ca 2ϩ pump, Na/Ca exchanger) (28), and (iv) maintenance of SR spatial organization and integrity (junctophilin) (29).…”
mentioning
confidence: 99%
“…They are involved in (i) calcium storage (calsequestrin) (25), (ii) signal transduction (triadin TD, junctin JC, mitsugumin-29, JP45) (23,24,26,27), (iii) calcium homeostasis (Ca 2ϩ pump, Na/Ca exchanger) (28), and (iv) maintenance of SR spatial organization and integrity (junctophilin) (29). Our previous studies (24,30) demonstrated that JP45, an integral protein constituent of the skeletal muscle SR junctional face membrane, interacts with Ca v 1.1 and the luminal calcium-binding protein calsequestrin (30,31). Ca v 1.1 and JP45 form a complex that is down-regulated during aging and may contribute to decayed muscle strength and physical disability in the elderly (31,32).…”
mentioning
confidence: 99%
“…Biochemical data indicate that in addition to RyRs, the JFM contains several protein constituents, including triadin, calsequestrin, junctin, histidine rich Ca 2þ binding protein (HRC), mitsugumin-29, junctophilin, 90 kDa protein or JP-45 (MacLennan and Wong, 1971;Hofmann et al, 1989;Caswell et al, 1991;Jones et al, 1995;Takeshima et al, 1998Takeshima et al, , 2000Froemming et al, 1999;Zorzato et al, 2000;Anderson et al, 2003). However, the JFM is also endowed with numerous other less abundant proteins having a molecular mass ranging between 20 and 120 kDa (Costello et al, 1986), whose identity and functional role are still obscure.…”
mentioning
confidence: 99%